Analisa Teknis Penggunaan B20, B30, dan B40 Pada Kapal Penumpang 2000 GT - Aldyn Clinton Partahi Oloan; Shahrin Febrian (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study provides an in-depth review of the technical and economic aspects of using B40 fuel and B30in 2000 GT motor passenger ships. Identifying patterns of diesel fuel consumption in ship operations is crucial for ferry fleets, especially in relation to efforts to achieve fuel efficiency during ship operations. In resolving existing problems, the efficiency study was completed through the application of technical, correlational-predictive, and comparative analytical approaches. The technical analytical approach was specifically applied in calculating engine characteristics related to fuel consumption, while the correlational-predictive approach was used to examine the correlation between engine characteristics and fuel variations and ship operating patterns. Meanwhile, the comparative approach was used to present a more comprehensive picture of the case study on the use of diesel fuel as fuel for the main engine on a 2000 GT ferry operating on the Padang Bai - Lembar route.